Application of Attachable Magnetic Nerve Stimulator in Intraoperative Facial Nerve Monitoring during Ear Surgery. (10th March 2020) - Oh, Se‐Joon; Choi, Sung‐Won; Lee, Seokhwan; Na, Han‐Seul; Sung, Eui‐Suk; Shin, Sung‐Chan; Lee, Byung‐Joo
Abstract : We developed an attachable magnetic nerve stimulator (AMNS) that connects the metallic instruments to a neurophysiological monitoring unit for monitoring the facial nerve (FN) during ear surgery and present our experiences with intraoperative neuromonitoring (IONM) of the FN using AMNS. The FN in 20 patients who underwent tympanomastoidectomy for chronic ear disease was examined. The electromyography (EMG) amplitudes of the FN using AMNS were assessed. The EMG amplitudes of the FN at 1.00‐mA stimulation during drilling were 265 ± 64 µV in the orbicularis oris and 288 ± 57 µV in the orbicularis oculi. The EMG amplitudes using AMNS attached to the surgical instruments under 0.35‐mA stimulus at the tympanic segment of the FN were 196 ± 43 µV in the orbicularis oris and 197 ± 41 µV in the orbicularis oculi. The application of continuous stimulation with burr and surgical instruments using the AMNS is feasible and effective for FN stimulation and identification.